Comparing the Effectiveness of Cognitive Behavioral Therapy and Schema Therapy on Externalizing Behaviors in Adolescents with High-Risk Behaviors - Ghafari Moghadam, Fahimeh; Dehghani Arani, Fateme; Zarghami, Elham (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of cognitive behavioral therapy and schema therapy on reducing externalizing behaviors in adolescents with high-risk behaviors.Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest control group and a two-month follow-up. The statistical population consisted of adolescents with high-risk behaviors referred to counseling centers of the Department of Education in Karaj in 2025. A total of 45 participants were selected through purposive sampling and randomly assigned into two experimental groups (cognitive behavioral therapy and schema therapy) and one control group, each comprising 15 participants. The experimental groups received eight sessions of group-based interventions, while the control group remained on a waiting list without intervention. Data were collected using the Achenbach-based Externalizing Behavior Questionnaire. Data analysis was conducted using SPSS version 26 at both descriptive and inferential levels, including repeated measures ANOVA and Bonferroni post hoc tests after verifying statistical assumptions.Findings: The results indicated that the main effect of group was not statistically significant (p > 0.05), whereas the main effect of time was significant (p < 0.001), demonstrating changes in externalizing behaviors across measurement stages. Furthermore, the interaction effect of time and group was statistically significant (p < 0.001), indicating differential changes among the groups over time. Bonferroni post hoc comparisons revealed that both cognitive behavioral therapy and schema therapy significantly reduced externalizing behaviors compared to the control group at posttest (p < 0.001), while no significant difference was observed between the two intervention groups (p > 0.05). Pairwise comparisons also showed that improvements were maintained at follow-up in both experimental groups.Conclusion: Both cognitive behavioral therapy and schema therapy were effective in reducing externalizing behaviors in adolescents with high-risk behaviors, with comparable levels of effectiveness and sustained outcomes over time.